Surface ultrastructure of gills in relation to the feeding ecology of an angler catfish Chaca chaca (Siluriformes, Chacidae). Issue 10 (28th July 2016) - Mistri, Arup; Verma, Neeraj; Kumari, Usha; Mittal, Swati; Mittal, Ajay Kumar
Abstract: Surface ultrastructure of the gills of the angler catfish Chaca chaca was investigated to unravel the adaptive modifications associated with the feeding ecology of the fish. The fish is often found in mud or in soft substrates where they remain buried both for protection and to feed. Gill rakers present on the gill arch in most fish species are absent in this fish. The absence of gill rakers are associated with the feeding habit of the fish and is considered to facilitate the swallowing of captured prey smoothly without any hindrance. Highly corrugated surface of the gill arch and gill filaments could be associated to retain water/mucus to prevent dessicassion of the fish. Papillae like epithelial protuberances each bearing a taste bud at its summit toward the pharyngeal side of the gill arch is associated with the sorting of the food. Large number of mucous goblet cells on the gill arch epithelium are considered to secret copious mucus to lubricate the prey for easy swallowing. In C. chaca the gill septa between gill filaments are reduced. This could enhance the flexibility and permit the free movement of the gill filaments. Extensive secondary lamellae and infrequent mucous goblet cells on secondary lamellae are associated to increase the surface area to enhance efficiency of gaseous exchange.